Women as department chairs at universities in South Africa and Britain - Zulu, Constance; Lemmer, Eleanor (University of the Free State, 2009)
The article reports on the findings of a qualitative inquiry into the lived experiences of a small sample of women chairs at universities in South Africa and Britain selected by purposeful sampling. Data were collected by means of video conference focus group interviews. Findings indicated that women department chairs require managerial competencies: rigorous scholarship as well as certain structures and procedures are necessary for the smooth management of a department. They face broader contextual issues in higher education owing to change, and the dual role influences their career experiences.

Hierdie artikel rapporteer oor ’n kwalitatiewe ondersoek na die bestuurservarings van vroulike voorsitters aan geselekteerde universiteite in Suid-Afrika en Brittanje, geïdentifiseer volgens doelgerigte steekproefneming. Data is met fokusgroeponderhoude per videokonferensie ingesamel. Die bevindings dui daarop dat vroulike voorsitters van departemente ’n behoefte het aan spesifieke bestuursvaardighede: nougesette vakkundigheid asook sekere strukture en prosedures is noodsaaklik vir effektiewe bestuur van ’n departement. Hulle het te kampe met breër kontekstuele vraagstukke weens verandering in hoëronderwys, en hul dubbele rol beïnvloed hul loopbaanervarings.
Keywords: Women in higher education; Gender identity in education; Educational leadership; Discrimination in higher education